2014
DOI: 10.1111/micc.12080
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Uterine Vascular Remodeling During Pregnancy

George Osol,
Lorna G. Moore

Abstract: Remodeling of the maternal uterine vasculature during pregnancy is a unique cardiovascular process that occurs in the adult and results in significant structural and functional changes in large and small arteries and veins, and in the creation of the placenta--a new fetomaternal vascular organ. This expansive, hypertrophic process results in increases in both lumen circumference and length, and is effected through a combination of tissue and cellular hypertrophy, endothelial and vascular smooth muscle hyperpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
229
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(242 citation statements)
references
References 89 publications
6
229
2
5
Order By: Relevance
“…Maximum remodeling of the main uterine artery occurs during late pregnancy and is associated with VSMC hypertrophy and hyperplasia [7][8][9][10]. This remodeling coincides with changes in the biomechanical properties of the artery, with arterial compliance changing as pregnancy advances [2]. Although there are considerable species differences, these biomechanical changes are attributed to alterations in the composition of the uterine artery wall.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Maximum remodeling of the main uterine artery occurs during late pregnancy and is associated with VSMC hypertrophy and hyperplasia [7][8][9][10]. This remodeling coincides with changes in the biomechanical properties of the artery, with arterial compliance changing as pregnancy advances [2]. Although there are considerable species differences, these biomechanical changes are attributed to alterations in the composition of the uterine artery wall.…”
Section: Introductionmentioning
confidence: 95%
“…The factors responsible for the remodeling of the uterine vasculature during pregnancy, particularly the main uterine artery, are influenced by a combination of local and systemic pregnancy-dependent factors [2,15]. Studies using pseudopregnant mice demonstrated that the conceptus is not involved in the initial remodeling response of the uterine artery [11], but as pregnancy progresses, the fetoplacental unit plays a major role in mediating expansion of the uteroplacental vasculature [16,17].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Rabbits are often used as experimental subjects in studies of prenatal effects on prenatal development because they are polytocous and they have hemochorial placentation (as in rat, house mouse and humans) (Faber and Hart, 1967;Flexner and Pohl, 1941;Osol and Mandala, 2009). Although, effects of prenatal T administration have been established in female rabbits (Bánszegi et al, 2009(Bánszegi et al, , 2010, no studies have been made on the effect of prenatal T administration on males.…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that pregnancy causes changes in systemic and uterine vessel reactivity and function through changes in both the endothelium and vascular smooth muscle cells [19][20][21][22]. It is therefore important to understand the mechanism by which hydralazine induces vasodilation during pregnancy.…”
Section: Introductionmentioning
confidence: 99%